Pulmonary Embolism in Pregnancy: Ultrasound-Assisted Catheter-Directed Thrombolytic Therapy for the Treatment of a Pulmonary Embolus—A Case Report - Michael G. Baracy, Jr; Olumide Olotu; Phillip Marchese; Marc Gosselin; Shyla Vengalil; Yang Pan (Maternal-Fetal Medicine)
Abstract. In the United States, pulmonary embolism (PE) accounts for approximately 10% of all pregnancy related deaths. The standard treatment for a patient with high-risk PE is systemic thrombolysis. Systemic thrombolysis in pregnancy is associated with the risk of maternal hemorrhage and fetal complications, including spontaneous abortion, preterm delivery, and fetal bleeding. Currently, there is limited evidence for a standardized approach for the treatment and management of intermediate- and high-risk PEs in pregnancy. A 36-year-old gravida 3 para 2002 woman at 31+1 weeks of gestation with a history of deep vein thrombosis in her prior pregnancy presented with shortness of breath. A computed tomography angiogram revealed a large pulmonary embolus with a saddle component that extended into the bilateral upper and lower lobes and into the secondary and tertiary pulmonary branches. A subsequent bedside echocardiogram demonstrated a dilated right ventricle with severely reduced right ventricular systolic function. The patient was successfully treated with bilateral ultrasound-assisted catheter-directed thrombolysis. She subsequently delivered a healthy male infant at term. Reported cases of ultrasound-assisted catheter-directed thrombolysis in pregnant patients is limited. Our case demonstrates that localized thrombolysis is a viable treatment option for life-threatening PE in pregnancy. Catheter-directed thrombolysis can be efficacious in treating intermediate- and high-risk PEs in pregnancy while simultaneously reducing the risk of bleeding complications.